Added value of combining VMAT with computer-selected patient-specific non-coplanar IMRT beams in radiotherapy for nasopharyngeal carcinoma and mediastinal lymphoma - Leitão, Joana Marques da Silva (2021)
Tese de mestrado integrado em Engenharia Biomédica e Biofísica (Radiações em Diagnóstico e Terapia), Universidade de Lisboa, Faculdade de Ciências, 2021